A technique for obtaining monokaryotic haploid hyphae of Ustilago tritici, causal agent of wheat loose smut - and A.K. SARBHOY, B. SHARIFNABI, NEENA MITTER (Indian Phytopathology, 2002)
Twenty isolates of Ustilago tritici [U. segetum var. tritici] were collected from various parts of northern India and used for monokaryotic haplont production. Teliospores from the infected wheat samples were surface sterilized and 150-250 mul of sterilized teliospore suspension was evenly spread on Petri dishes containing 1.5-2 mm thick, 1.5% water agar and DL-aspartic acid (0.147 mg/ml water). The Petri dishes were incubated at 20â„ƒ for about 30 hours. Dikaryon formation was observed and subsequently 1 cm2 blocks of medium from these plates were transferred to plates of 1/5 normal nutrient concentration of potato dextrose agar and incubated in the refrigerator overnight. The squares were then transferred to another layer of 1/5 PDA pre-warmed to25?and kept at this temperature for 4-6 hours. Monokaryotic haploid hyphae were obtained and isolated by microsurgery with very thin Pasteur pipettes and transferred to a thick layer of 1/5 PDA and kept at 20? Growth of haplonts was relatively slow and was visible only after 4-5 days. After 2 weeks, the verrucose colonies of fungus which were dense, cream to pinkish cream, could be seen. The mycelial mass production of the mycelium of haploid hyphae can be obtained by inoculation of potato sucrose broth in shaker incubation at 130 rpm, 20?for 14-20 days. This technique was effective in obtaining monokaryotic haploid hyphae for all 20 isolates of U. segetum var. tritici.